2007
DOI: 10.1111/j.1440-1797.2007.00795.x
|View full text |Cite
|
Sign up to set email alerts
|

Is it time to revisit residual renal function in haemodialysis? (Review Article)

Abstract: SUMMARY:Residual renal function (RRF) is not currently emphasized for patients undergoing haemodialysis (HD). The role of RRF is well recognized in the peritoneal dialysis population as studies have clearly demonstrated a survival benefit with preservation of RRF. There is however, data to suggest that RRF is important in HD patients as well. Contemporary HD therapies using high flux biocompatible synthetic dialysers, bicarbonate buffered ultrapure dialysis fluids with ultrafiltration control appear to allow b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 74 publications
0
5
0
2
Order By: Relevance
“…The presence of residual native kidney function is associated with improved survival in dialysis patients (1)(2)(3)(4)(5)(6). Residual function is also associated with better nutrition, less evidence of inflammation, less cardiac hypertrophy, and better quality of life (5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of residual native kidney function is associated with improved survival in dialysis patients (1)(2)(3)(4)(5)(6). Residual function is also associated with better nutrition, less evidence of inflammation, less cardiac hypertrophy, and better quality of life (5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Preservation of residual kidney function is well recognised as a major goal in PD but is in most places not a major focus of HD practice. There is however a growing recognition of the importance of residual kidney function to outcomes in HD, and a movement to place more emphasis on this in dialysis practice . Fluid control, need for erythropoiesis‐stimulating agents and middle molecule clearance are all factors dependent in large part on residual kidney function .…”
Section: Discussionmentioning
confidence: 99%
“…For patients on dialysis it has been shown that there is benefit from preservation of even minimal residual renal function, and that ICAs may further diminish renal function in these patients. The authors recommend that ICAs should be contraindicated in these patients (46,47). Current data suggest that use of GBCAs selected for low risk of NSF have an associated NSF incidence that remains too small to measure, even in patients with severe renal disease.…”
Section: Contrast-induced Nephropathy (Cin)mentioning
confidence: 99%